Ixmyelocel-T for patients with ischaemic heart failure: a prospective randomised double-blind trial. Issue 10036 (11th June 2016) - Patel, Amit N; Henry, Timothy D; Quyyumi, Arshed A; Schaer, Gary L; Anderson, R David; Toma, Catalin; East, Cara; Remmers, Ann E; Goodrich, James; Desai, Akshay S; Recker, David; DeMaria, Anthony; et al.
Summary: Background: Ixmyelocel-T is an expanded, multicellular therapy produced from a patient's own bone marrow by selectively expanding two key types of bone marrow mononuclear cells: CD90+ mesenchymal stem cells and CD45+ CD14+ auto-fluorescent+ activated macrophages. Early phase clinical trials suggest that intramyocardial delivery of ixmyelocel-T might improve clinical, functional, symptomatic, and quality-of-life outcomes in patients with heart failure due to ischaemic dilated cardiomyopathy. We aimed to assess the safety and efficacy of catheter-based transendocardial injection of ixmyelocel-T cell therapy in patients with heart failure and reduced ejection fractions. Methods: In this randomised, double-blind, placebo-controlled phase 2B trial (ixCELL-DCM), patients from 31 sites in North America with New York Heart Association class III or IV symptomatic heart failure due to ischaemic dilated cardiomyopathy, who had left ventricular ejection fraction 35% or less, an automatic implantable cardioverter defibrillator, and who were ineligible for revascularisation procedures were randomly assigned (1:1) to receive ixmyelocel-T or placebo at the time of bone marrow aspiration and followed for 12 months. Randomisation was done through an interactive (voice/web) response system. The pharmacist, treating physician, and coordinator at each site were unblinded, but the the follow-up team was completely blinded. The primary endpoint was a composite of all-cause death, cardiovascular admission to hospital, and unplanned clinic visits to treat acute decompensated heart failure based on the blinded adjudication of an independent clinical endpoint committee. Primary efficacy endpoint analyses and safety analyses were done by modified intention to treat. This trial is registered withClinicalTrials.gov, numberNCT01670981 . Findings: Between April 2, 2013, and Jan 28, 2015, 126 participants were randomly assigned to receive either ixmyelocel-T (n=66) or placebo (n=60). 114 (90%) patients comprised the modified intention-to-treat population and 109 (87%) patients were included in the per-protocol primary efficacy analysis (58 in the ixmyelocel-T group and 51 in the placebo group). The primary efficacy endpoint was observed in 47 patients: 50 events in 25 (49%) of 51 patients in the placebo group and 38 events in 22 (38%) of 58 patients in the ixmyelocel-T group, which represents a 37% reduction in cardiac events compared with placebo (risk ratio 0·63 [95% CI 0·42–0·97]; p=0·0344). 41 (75%) of 51 participants in the placebo group had serious adverse events versus 31 (53%) of 58 in the ixmyelocel-T group (p=0·0197). Interpretation: To the best of our knowledge, ixCELL-DCM is the largest cell therapy study done in patients with heart failure so far. The transendocardial delivery of ixmyelocel-T in patients with heart failure and reduced ejection fraction due to ischaemic dilated cardiomyopathy resulted in a significant reduction in adjudicated clinical cardiac events compared with placebo leading to improved patient outcomes. Funding: Vericel Corporation.